2020
DOI: 10.1530/rep-20-0156
|View full text |Cite
|
Sign up to set email alerts
|

PDIA3 regulates trophoblast apoptosis and proliferation in preeclampsia via the MDM2/p53 pathway

Abstract: Protein disulfide isomerase 3 (PDIA3) is a chaperone protein that modulates the folding of newly synthesized glycoproteins, has isomerase and redox activity, and has been implicated in the pathogenesis of many diseases. However, the role of PDIA3 in pregnancy-associated diseases remains largely unknown. Our present study reveals a key role for PDIA3 in the biology of placental trophoblasts from women with preeclampsia (PE). Immunohistochemistry and Western blot analysis revealed that PDIA3 expression was decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Even though it was not in the top 50 DEGs and was not part of the top 12 genes we have focused on, it must be noted that PDIA3 is down-regulated in ERAP2N-expressing TCs. It was reported that PDIA3 expression was decreased in the TCs from women with PE, and decreased PDIA3 expression induced trophoblast apoptosis and repressed trophoblast proliferation by regulating the MDM2/p53/p21 pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…Even though it was not in the top 50 DEGs and was not part of the top 12 genes we have focused on, it must be noted that PDIA3 is down-regulated in ERAP2N-expressing TCs. It was reported that PDIA3 expression was decreased in the TCs from women with PE, and decreased PDIA3 expression induced trophoblast apoptosis and repressed trophoblast proliferation by regulating the MDM2/p53/p21 pathway [38].…”
Section: Discussionmentioning
confidence: 99%
“…The establishment and maintenance of pregnancy poses great challenges to the maternal immune system. Uncoordinated maternal immunization, especially in the first trimester of pregnancy, will be a potential cause of a series of pregnancy complications (47,48). Currently, immunotherapy has been applied to the treatment of a variety of reproductive diseases, such as recurrent spontaneous abortion (RSA) and recurrent implantation failure (RIF) (49), while the immunotherapy against PIH still needs a long way to go.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Kalkat et al reported that the balance of BCL2 family proteins was altered towards cell death in preeclampsia ( Kalkat et al 2013 ). Recent studies have focused on trophoblast apoptosis caused by molecular dysfunction that leads to the disease ( Guo et al 2017 , Wang & Yan 2018 , Mo et al 2020 ). CLDN1 has been shown to be involved in apoptosis via alterations in the expression levels of Bcl-2 and Bax ( Singh et al 2012 , Zheng et al 2019 ), which was not detected in our study (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%